Factors contributing to the adequate vitamin A status and poor anthropometric status of 24-59-month-old children from an impoverished Northern Cape community - Nel, Jana (Stellenbosch : Stellenbosch University, 2013)
Thesis (MNutr)--Stellenbosch University, 2013.